One struggle, one fight! Human freedom, animal rights! : grassroots animal rights activisim : incorporating animal liberation and general liberation ideologies : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Anthropology at Massey University - Beynon, Penelope A (Massey University, 2003)
This thesis reports original research conducted among grassroots animal rights activists (GARAs) in Dunedin, New Zealand. The principle finding is that GARAs are unique in that they operate according to a dual-ideology of animal and general liberation. Much has been written about animal rights activism and the animal protection movement but few differentiate branches and groups beyond the basic philosophical distinctions of welfarists and rightsists. This study argues that differences in the organisational, lifestyle and tactical choices of specific groups represent more than simple differences in tastes, and proposes a Six-Axis model as an appropriate tool for investigating ideological positioning that may indicate reasons for difference. Drawing on information gathered through participant-observation and in-depth interviews, this study applies the Six-Axis model and explores the experiences GARAs have in grassroots groups and with animals. KEYWORDS: Animal Rights, Grassroots Activism, Animal Protection Movement, Social Movement, Post-Citizenship Movement, Liberation Movement.
Keywords: Animal rights activists; Animal rights movement; Animal rights; Grassroots groups